Determinants of information and communication technology usage among village administrators in Malaysia using extended technology acceptance model - Abu Hassan, Musa; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva (Medwell Journals, 2012)
ICT projects in Malaysia have been one of the impetuses for achieving development in this country. Parallel with the ICT development in Malaysia, ICT usage among the Malaysian has increased significantly. Nonetheless, things are different in the rural areas where past studies have shown that ICT usage among the rural community in Malaysia is still discouraging. Albeit this fact are the same situation can be identified among the village administrators and what are the factors that impinge their ICT usage? Purportedly, as the leaders of the rural community they should use ICT in order to encourage the rural community to use ICT. This quantitative study used questionnaire to gather information. Through a multi-stage random sampling, a total of 240 village administrators from four states in Peninsular Malaysia have been selected as the respondents. In general, ICT has been used moderately among the village administrators. All of seven factors of Extended Technology Acceptance Model studied have been detected to be positively and significantly related with ICT usage while self-efficacy was identified as the main contributor towards ICT usage. A number of recommendations and discussions have been highlighted and expectantly it can aid the concern parties and policy makers in drawing plans for strengthening the ICT usage among the rural community leaders.